(untitled) - Goddard, Cliff (Oxford, 1998)
This book is a lively and clearly-written introduction to the study of meaning in language, and to the links between language, meaning, and culture. This is the first textbook introduction to cross-cultural, cross-linguistic semantics.
Keywords: Semantics